2022
DOI: 10.1002/ajs4.240
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization's impacts on age‐friendly policymaking: A case study on Australia

Abstract: This paper reflects on whether and how the World Health Organization (WHO) inspires age‐friendly policymaking across different levels of government. This is done via a case study in which we analyse the policies of Australia's three‐tiered federated government system against the WHO's eight core age‐friendly cities domains. Findings suggest that membership of the Global Network of Age‐Friendly Cities and Communities did not appear to overtly inspire the development of age‐friendly policies across Australian go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Phase 1 is about research questions (RQ). They are organized around four areas: (a) Quartile or Sinta levels of journals (RQ1), documentary characteristics geographical location (RQ2), and research methodologies used (RQ3); (b) domain and dimension of an age-friendly environment identified in the literature (RQ4) [1,3]; (c) the factors that contribute to successful implementation (RQ5) [9]; and (d) the outcomes (RQ6) [10] and impacts (RQ7) [11] of age-friendly environment initiatives in the analyzed studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase 1 is about research questions (RQ). They are organized around four areas: (a) Quartile or Sinta levels of journals (RQ1), documentary characteristics geographical location (RQ2), and research methodologies used (RQ3); (b) domain and dimension of an age-friendly environment identified in the literature (RQ4) [1,3]; (c) the factors that contribute to successful implementation (RQ5) [9]; and (d) the outcomes (RQ6) [10] and impacts (RQ7) [11] of age-friendly environment initiatives in the analyzed studies.…”
Section: Methodsmentioning
confidence: 99%
“…As a systematic literature review, this study found the age-friendly environment concept is still in emerging studies. The basic foundation of the concept which come from WHO Europe office [11] is going to implement in other studies about environment and city [1], health, well-being, and social impact [10,15], policy [3,16], and community [9]. The recent studies about age-friendly environment concept also proposed inclusive model in vulnerable areas [17], social participation [18] and sustainable development goals [19].…”
Section: Outcomes and Impacts Of Age-friendly Environment Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the NDIS and the My Aged Care program can recommend and co-fund home modifications as part of their respective support assessments, many barriers exist to prevent them from being put into practice. Different levels of external approvals-from housing providers and/or owners' corporations in strata-titled properties-may be required in order to implement modifications (Liu, Atkins et al 2022). There is also evidence that older properties may be structurally unable to support modifications due to poor initial construction and/or lack of maintenance.…”
Section: Population Groups With Specific Needsmentioning
confidence: 99%